Effect of laser scanning speed on geometrical features of Nd:YAG laser machined holes in thin silicon nitride substrate. Issue 3 (15th February 2017) - Zhang, Jinyang; Long, Ying; Liao, Shixian; Lin, Hua-Tay; Wang, Chengyong
Abstract: 0.5 mm thick Silicon nitride (Si3 N4 ) substrates with MgO-Y2 O3 additives were employed for hole machining study with a Nd:YAG two-dimensional laser machining (cutting) system. The effects of laser scanning speed on features of the machined holes such as hole diameter, hole circularity, taper angle, heat affected zone (HAZ), recast layer, and micro-cracks were studied. The results show that the diameters at the front side are larger than the back side for all holes machined at different spot scanning speed. The taper angle of the machined holes decreases, while the hole circularity increases with the increase of the spot scanning speed. In addition, the heat-affected-zone (HAZ) was observed clearly around the back side of drilled holes, whose area decreases with the increase of the laser spot scanning speed. The result shows that the HAZ is the largest when the laser scanning speed is 20 mm/min. Nevertheless, the machined hole did not completely cross through the thickness of the substrate when the laser scanning speed was 60 mm/min. To obtain holes with relatively good quality, laser scanning speed should be controlled between 30 mm/min and 50 mm/min.